A Bioinspired Hemostatic Powder Derived from the Skin Secretion of Andrias davidianus for Rapid Hemostasis and Intraoral Wound Healing. Issue 3 (23rd November 2021) - Zhang, Ximu; Jiang, Lin; Li, Xian; Zheng, Liwen; Dang, Ruyi; Liu, Xiang; Wang, Xiaoping; Chen, Liling; Zhang, Yu Shrike; Zhang, Jixi; Yang, Deqin
Abstract: High‐performance hemostasis has become increasingly essential in treating various traumas. However, available topical hemostats still have various drawbacks and side‐effects. Herein, hemostatic powders derived from the skin secretion of Andrias davidianus (SSAD) with controllable particle size are prepared using feasible frozen‐ball milling following lyophilization for hemorrhage‐control. Scanning electron microscopy, rheometry, and Brunauer–Emmett–Teller test are used to characterize the coagulation‐promoting surface topography, rheological properties, and porous structure of the SSAD particles. The blood‐coagulation assays showed that the SSAD powders can induce blood‐absorption in a particle size‐dependent manner. Particle sizes of the SSAD powders larger than 200 µm and smaller than 800 µm greatly affect the blood‐clotting rate. Associated with the thromboelastography (TEG) and amino acid/protein composition analyses, the accessibility and diffusion of blood are mainly dependent on the wettability, adhesivity, and clotting factors of the SSAD particles. Rapid hemostasis in vivo further involves three hemorrhage models (liver, femoral artery, and tail) as well as an oral wound model, which suggest favorable hemostatic and simultaneous regenerative effects of the SSAD hemostatic powder. Considering its degradability and good biocompatibility, SSAD can be an optimal candidate for a new class of inexpensive, natural, and promising hemostatic and wound‐dressing agent. Abstract : Hemostatic powders derived from the skin secretion of Andrias davidianus (SSAD) with controllable particle sizes are prepared, inducing blood‐absorption in a particle size‐dependent manner. Featuring favorable hemostatic and simultaneous regenerative effects, along with degradability and good biocompatibility, the SSAD hemostatic powder can be a potential candidate as a new class of inexpensive and natural hemostatic and wound‐dressing agent.